Marketing with AI - Singh, Shiv (--For dummies., 2024)
"Marketing with AI For Dummies is your introduction to the revolution that's occurring in the marketing industry, thanks to artificial intelligence tools that can create text, images, audio, video, websites, and beyond. This book captures the insight of leading marketing executive Shiv Singh on how AI will change marketing, helping new and experienced marketers tackle AI marketing plans, content, creative assets, and localized campaigns. You'll also learn to manage SEO and customer personalization with powerful new technologies. This easy-to-understand Dummies guide is perfect for marketers at all levels, as well as those who only wear a marketing hat occasionally. Whatever your professional background, Marketing with AI For Dummies will usher you into the future of marketing."--